Impacts of festivals and events on residents’ well-being - Yolal, M.; Gursoy, D.; Uysal, Muzaffer; Kim, H.; Karacaoglu, S. (Elsevier Ltd, 2016)
This study investigated how residents’ participation in local festivals may influence their subjective-well-being and their quality of life. Using data collected from local attendees of a film festival, this study examined the relationship between socio-cultural impacts of a festival and subjective well-being of local residents. Findings revealed that while community benefits and cultural/educational benefits are positive predictors of subjective well-being of residents, quality life concerns were found to have negative impact on the well-being of residents. Findings also revealed no significant relationship between community resource concerns and subjective well-being of residents.